PERAN PENDIDIKAN TINGGI DALAM PEMBERDAYAAN KOMUNITAS LOKAL: MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK SOLUSI BERKELANJUTAN PADA MAHASISWA INSTITUT PARIWISATA DAN BISNIS INTERNASIONAL - Ni Made Rinayanthi; Gede Sidi Artajaya (Widyadari, 2025)
Higher education plays a crucial role in empowering local communities, especially in creating sustainable solutions to the challenges faced by these communities. One proven model of learning that effectively achieves this goal is project-based learning. In this model, students collaborate with faculty members and members of the local community to design, implement, and evaluate projects aimed at providing direct benefits to the community. This article discusses the important role of higher education in empowering local communities through project-based learning models. Through this approach, students not only gain practical experience in applying the knowledge acquired in the classroom but also assist in identifying and addressing the challenges faced by the local community. By strengthening the relationship between universities and communities, the project-based learning model not only enriches students' learning experiences but also helps to enhance the well-being and sustainability of local communities. Case studies presented in this article will illustrate the practical implementation of this learning model and its impact on empowering local communities and the contributions made by higher education in creating sustainable solutions to social, economic, and environmental issues.